(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Our schools have to make physical education a truly integral subject of school curriculum. The main objectives of this study were to measure the Attitude of Higher Our schools have to make physical education a truly integral subject of school Secondary students studying in Kendriya Vidyalayas of Maharashtra states towards physical education. The researchers selected 25 schools on the basis of cluster sampling out of 38 schools having at least 1-3 streams viz. science, commerce and arts for study. Thus 28 students were selected randomly from each school, and a sample of total 700 subjects of Kendriya Vidyalayas selected randomly from the higher secondary classes of each schools. An Attitude scale based on 'Likert five point scale' (1932) was used as a tool for data collection. Mean, S.D., T- test and ANOVA were used to analyse and interpret the data. The main findings of the study were: 1) Majority of students had favorable attitude towards physical education in the Kendriya Vidyalayas of Maharashtra State. 2) Male and female students did not differ significantly in respect to their attitude toward physical education. 3) Sportsmen and non-sportsmen differed significantly in respect to their attitude toward physical education 4) Student belonging to different streams viz. Science, Commerce and Arts streams did not differ significantly in respect to their attitude regarding physical education.